Development of MATLAB Code for Gear Ratio Design and Evaluation in Vehicle Transmission Systems - Irawan, Yosua Heru (Institut Teknologi Nasional Yogyakarta, 2024)
This article presents the development of a MATLAB code for the design and evaluation of gear ratios in vehicle transmission systems, with the objective of optimizing acceleration and fuel efficiency. The MATLAB tool incorporates analysis of engine power, torque, and resistance forces to calculate gear ratios and simulate vehicle performance. Test results indicate that the developed MATLAB code successfully predicts vehicle dynamics, including maximum speed and acceleration performance across different gear ratios. The test design shows that the vehicle can achieve a top speed of 285 km/h at 5th gear, which exceeds design requirements, while maintaining efficient acceleration throughout the range of gears. This code is also suitable for use in educational settings, providing students and lecturers with a powerful method to study and enhance vehicle transmission systems. Future work can further explore its applications in system optimization in automotive engineering.